Healthiness matters: Approach motivation for healthy food in overweight and obese individuals. (1st January 2022) - Moore, Sophia; Rudaizky, Daniel; MacLeod, Colin; Dondzilo, Laura
Abstract: It is well documented that approach tendencies for appetitive substances play a role in certain unhealthy patterns of consumption. However, it remains uncertain whether overweight individuals differ from healthy-weight individuals in terms of their tendency to approach unhealthy foods. Thus, the present study aimed to empirically test the hypothesis that overweight individuals are characterised by an elevated behavioural tendency to approach unhealthy food, rather than healthy food, as compared to healthy-weight individuals. Participants were forty-one overweight individuals (Mean BMI = 30.40 kg/m 2 ) and forty-five healthy-weight individuals (Mean BMI = 22.17 kg/m 2 ) aged between 17 and 47. They completed an Approach-Avoidance Task to assess behavioural approach-avoidance tendencies towards healthy and unhealthy food. Contrary to the hypothesis under test, results revealed a greater approach tendency towards healthy food in overweight individuals, as compared to healthy-weight individuals, whereas there were no group differences in behavioural approach-avoidance tendencies towards unhealthy food. These novel findings suggest that overweight individuals are characterised by an approach motivation for healthy food. We provide suggestions concerning how future researchers can build on these findings to test whether this approach tendency contributes to consumption behaviour in overweight individuals.